Responding to the Anthropocene Perspectives from Twelve Academic Disciplines - Münster, Ursula (Spartacus Forlag AS / Scandinavian Academic Press, 2023)
The Anthropocene - the era of humans - refers to a time when humanity has left its indelible stamp on the planet, including its geology and biogeochemistry. Understanding the Anthropocene, where the risk of irreversible and catastrophic ecological damage looms on the horizon, is a daunting task and solutions seem to be difficult to come by. What we offer in this book consists of fifteen perspectives on the Anthropocene written by scholars with backgrounds in over a dozen academic disciplines - archaeology, biology, geology, cultural history, literature, art history, science and technology studies, anthropology, political ecology, geography and law. Together, they offer tools enabling us to grasp the Anthropocene as a multifaceted phenomenon that requires attention from across the social and natural sciences as well as the humanities. Unlike most academic texts, these chapters are written in a personal and engaging style indicating not only that the Anthropocene is a worthy subject of scholarly attention, but that its implications are existentially important to the authors, who are not just researchers, but also global citizens.